Briefing: Bringing clarity and new understanding of smart and modular integrated construction. Issue 1 (28th April 2021) - Pan, Wei; Zhang, Zhiqian; Yang, Yi
Abstract : Modular construction has been promoted worldwide, with well demonstrated benefits. Modular integrated construction (MiC) was recently established in Hong Kong with the focus on integrated solutions to address high-rise buildings in high-density cities for productivity and competitiveness. Nevertheless, insufficient and inconsistent understanding exists. The University of Hong Kong has recently launched A Glossary of Modular Integrated Construction, which defines and illustrates over 170 terms related to MiC, off-site construction and smart project delivery, aiming at synergised understanding. The Glossary brings clarity and new understanding of modular and smart construction to the industry and community. With a focus on future building development in high-rise high-density contexts, the Glossary should become an important aid for achieving wider adoption of modular construction and smart technologies.